Changes in the Scandinavian model from bureaucratic command to interorganizational negotiation - Bogason, Peter (1998)
Scandinavian local government is increasingly changing its organizational pattern away from the principles of local centralized bureaucratic control that were held sacred after the reforms of the 1960s and 1970s - reforms that made local government the building block for the welfare `state'. Organizational fragmentation is taking place, making room for both new managerial styles similar to those of the New Public Management, featuring contracting out and similar market-like arrangements, and for democratic initiatives which place service users in command of service institutions. Such developments call for new approaches to the study of local government, approaches that take interorganizational relations more directly into account. Suggestions about such an approach are made, based on studies of intergovernmental relations. Distinctions are made between intergovernmental politics which is concerned with symbolic values linked to the status of an organization, and intergovernmental management where processes of making do are seen as most important. In spite of the managerial fashion for strategic goal-setting, it is expected that the new political actors are more interested in day-to-day results and thus challenge politicians, moving them away from the abstract goals in favour of advancing and monitoring actual accomplishments. This increases the need to understand network relations and, in turn, may yield better understanding on the part of citizens of how local politics and management works. - Reproduced
Keywords: Local government - Scandinavian; Local government